Development of Ecological Environment Monitoring Network System in China - Qiao Wang; Shaomin Liu; Guoqiang Wang; Yinglan A; Baolin Xue; Ziwei Xu; Jin Wu (中国工程科学)
Ecological environment monitoring is an essential foundation for ecological and environmental protection and will play a key role in building a grand ecological and environmental protection and governance framework. Although China has built a large-scale, comprehensive, and well-structured ecological environment monitoring network, it is insufficient to meet the major national demands of the new era, such as reducing pollution and carbon emissions, ecological protection and restoration, and addressing climate change. This study elaborates on the development demand of China for an ecological environment monitoring network system, outlining the current status of the system in terms of monitoring network, monitoring technologies and equipment, monitoring indicators, and monitoring applications. It further identifies existing problems, including the lack of an integrated ecological environment monitoring network, shortage of independent and advanced monitoring equipment, delayed development of indicators and insufficient data processing and sharing, as well as lack of an integrated coordination and support mechanism. The study argues for several key tasks to address these problems, including integrating the ecological environment monitoring network, advancing the independent development of monitoring technologies and equipment, unifying the monitoring indicator system, and integrating the applications of the ecological environment monitoring network. The study also proposes the following recommendations: (1) building an ecological environment monitoring system that integrates air, space, land, and sea, (2) promoting the independent research and development of monitoring equipment and its application, (3) establishing a new system for ecological environment monitoring standards, technologies, and services, (4) ensuring the healthy development of the integrated monitoring network system, and (5) launching major scientific projects and prioritizing monitoring applications in typical regions. This study is expected to serve as a reference for the research, construction, and application of the integrated ecological environment monitoring network system in China.